Burr formation and elimination in micromilling processes. (17th July 2007) - Jackson, Mark J.; Robinson, Grant M.; Whitfield, Michael D.; Ahmed, Waqar
Machining at any scale usually produces burrs on surfaces; burrs are unwanted and add cost to the part. In general machining parameters are optimised to prevent burr formation, the cutting tool is assumed to be worn and is changed when burrs appear. When burrs appear on the part they must be deburred. At the micro scale deburring has been shown to be impractical because excessive dimensional errors and high tensile residual stresses are induced into the part. This study examines three methods of preventing burr formation: using coated tools to prevent tool wear; selecting a workpiece with a low amount of dislocations to prevent plastic deformation; and using machinable vice jaws to manipulate the flow stress. All these methods succeeded in suppressing burr formation.